Protection against muscle damage in competitive sports players: The effect of the immunomodulator AM3 - Cordova, A.; Martin, J. F.; Reyes, E.; Alvarez-Mon, M. (Journal of Sports Sciences, 2004)
Strenuous physical exercise of the limb muscles commonly results in damage, especially when that exercise is intense, prolonged and includes eccentric contractions. Many factors contribute to exercise-induced muscle injury and the mechanism is likely to differ with the type of exercise. Competitive sports players are highly susceptible to this type of injury. AM3 is an orally administered immunomodulator that reduces the synthesis of proinflammatory cytokines and normalizes defective cellular immune fractions. The ability of AM3 to prevent chronic muscle injury following strenuous exercise characterized by eccentric muscle contraction was evaluated in a double-blind and randomized pilot study. Fourteen professional male volleyball players from the First Division of the Spanish Volleyball League volunteered to take part. The participants were randomized to receive either placebo (n=7) or AM3 (n=7). The physical characteristics (mean+/-s) of the placebo group were as follows: age 25.7+/-2.1 years, body mass 87.2+/-4.1 kg, height 1.89+/-0.07 m, maximal oxygen uptake 65.3+/-4.2 ml.kg(-1).min(-1). Those of the AM3 group were as follows: age 26.1+/-1.9 years, body mass 85.8+/-6.1 kg, height 1.91+/-0.07 m, maximal oxygen uptake 64.6+/-4.5 ml.kg(-1).min(-1). All participants were evaluated for biochemical indices of muscle damage, including concentrations of aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, creatine kinase (CK) and its MB fraction (CK-MB), myoglobin, lactate dehydrogenase, urea, creatinine and gamma-glutamyltranspeptidase, both before and 30 days after treatment (over the peak of the competitive season). In the placebo group, competitive exercise (i.e. volleyball) was accompanied by significant increases in creatine kinase (494+/-51 to 560+/-53 IU.l(-1), P < 0.05) and myoglobin (76.8+/-2.9 to 83.9+/-3.1 microg.l(-1), P < 0.05); aspartate aminotransferase (30.8+/-3.0 to 31.1+/-2.9 IU.l(-1)) and lactate dehydrogenase (380+/-31 to 376+/-29 IU.l(-1)) were relatively unchanged after the 30 days maximum effort. AM3 not only inhibited these changes, it led to a decrease from baseline serum concentrations of creatine kinase (503+/-49 to 316+/-37 IU.l(-1), P < 0.05) and myoglobin (80.1+/-3.2 to 44.1+/-2.6 IU.l(-1), P < 0.05), as well as aspartate aminotransferase (31.1+/-3.3 to 26.1+/-2.7 IU.l(-1), P < 0.05) and lactate dehydrogenase (368+/-34 to 310+/-3 IU.l(-1), P < 0.05). The concentration of CK-MB was also significantly decreased from baseline with AM3 treatment (11.6+/-1.2 to 5.0+/-0.7 IU.l(-1), P < 0.05), but not with placebo (11.4+/-1.1 to 10.8+/-1.4 IU.l(-1)). In conclusion, the use of immunomodulators, such as AM3, by elite sportspersons during competition significantly reduces serum concentrations of proteins associated with muscle damage.